Resiliensi psikologis mahasantri baru UIN Malang: Pendekatan konseling islam dalam mengatasi culture shock di asrama - Nurhalizah, Siti; Ardani, Tristiadi Ardi (Maliki Interdisciplinary Journal, 2026)
New mahasantri at Universitas Islam Maulana Malik Ibrahim Malang face adaptation challenges due to the dormitory system requiring them to live and engage fully in the ma’had environment. Environmental changes, social norms, and academic and religious demands often trigger culture shock, leading to stress, anxiety, and adjustment difficulties. This study aims to examine the role of psychological resilience and Islamic counseling in overcoming culture shock among new mahasantri. The method used is a literature review of relevant scholarly sources. The findings show that psychological resilience acts as a protective factor that helps individuals regulate emotions, maintain optimism, and adapt effectively. Islamic counseling contributes by integrating psychological and spiritual aspects, including strengthening religiosity, fostering meaning in life, and applying religious coping strategies such as dhikr, prayer, and self-reflection. The integration of both approaches provides a holistic solution in addressing culture shock and enhancing psychological and spiritual well-being.